Identity exploration for maker educators: constructing meaning in after-school environmental science. Issue 4 (8th August 2022) - Petrovich, Mark E.; Barany, Amanda; Shah, Mamta; Foster, Aroutis
Abstract: Maker-based learning activities offer benefits to both students and educators; however, there exist few research examples that examine how educators enact a process of identity exploration when implementing maker activities in their instruction. The Projective Reflection framework was used to assess three science educators' identity exploration as they engaged in professional development sessions on maker education. Teacher data was visualized using epistemic network analysis and supplemented with qualitative examinations to understand how teachers engaged in identity exploration over time. Findings illustrated shifts toward more specific and balanced conceptualizations of self as educators gained skill in the intentional examination of roles.